Pelatihan Penggunaan Aplikasi Wordwall untuk Menunjang Evaluasi Pembelajaran di Sekolah - Latjompoh, Masra; Usman, Nurul Fajryani (Damhil: Jurnal Pengabdian kepada Masyarakat, 2023)
The very rapid development of technology demands changes in all aspects of education. Developing technology encourages teachers to be able to develop learning media. However, in fact, some teachers have not been able to develop the ability to use learning media as learning aids, especially learning evaluation tools. One of the learning media that can be used by teachers to assist learning activities, especially learning evaluation, is the wordwall application. Wordwall is a piece of software that works online and is used as a game-based learning medium for kahoots, quizzes, and so on. The wordwall application is unique as an assessment tool in the form of multiple choice questions (quizzes). Crossword puzzles, select cards or images according to match, match the correct answer (match search), etc., so that assessment tools can be used for assessmentdaily.